A two-step reaction mechanism of oxygen release from Pd/CeO2: mathematical modelling based on step gas concentration experiments - Christou, S.Y; Costa, Costas; Efstathiou, A.M. (My University, 2004)
A mathematical model has been developed to study the transient release of oxygen from a 1 wt% Pd/CeO2 catalyst in the 450–550 °C range based on alternate step concentration switches between CO and O2. A two-step reaction mechanism that involves the reaction of gaseous CO with the oxygen species of PdO and of the back-spillover of oxygen from ceria to the oxygen vacant sites of surface PdO has been proven to better describe the CO and CO2 transient response curves. The proposed mathematical model allows the estimation of the transient rates of the CO oxidation reaction and of the back-spillover of oxygen process. It also allows the calculation of the intrinsic rate constant k 1 (s−1) of the Eley–Rideal step for the reaction of gaseous CO with surface oxygen species of PdO to form CO2. An activation energy of 10.1 kJ/mol was estimated for this elementary reaction step. In addition, an apparent rate constant kapp2(s−1) was estimated for the process of back-spillover of oxygen.
Keywords: Transient CO oxidation; Oxygen storage capacity; Oxygen back-spillover